Development of the Arabian-Nubian Shield along the Marsa Alam-Idfu transect, Central-Eastern Desert, Egypt: geochemical implementation of zircon U-Pb geochronology - Sherif Mansour; Noriko Hasebe; Kamal Abdelrahman; Mohammed S. Fnais; Mohamed A. Gharib; Rabiou Habou; Akihiro Tamura (Geochemical Transactions)
Abstract The magmatic complex along the Marsa Alam-Idfu transect, Central-Eastern Desert of Egypt, represents the northern segment of the Arabian–Nubian Shield (ANS), which developed within the framework of the East African Orogen. The basement rocks of the Arabian-Nubian Shield have been developed through three distinct phases of magmatic activity: the island-arc, the syn-orogenic, and the post-orogenic phases. Transitioning of the magmatic phases from the syn-orogenic to the post-orogenic, identifies changing the tectonic regime from a compressional to an extensional setting. The scarcity of comprehensive regional geochronological data that rely on precise isochron methods, such as the zircon U-Pb technique, could limit the comprehensive understanding of this region’s geological and tectonic history. That would raise a number of uncertainties ranging from the timing of the different magmatic activities and timing of changes in the tectonic regime to the existence of the pre-Pan-African crust in the CED. Our study provides new insights into the aforementioned uncertainties through zircon U-Pb dating of different rock units along the Marsa Alam-Idfu transect, CED, Egypt. The resulting ages ranged from 729 ± 3 Ma to 570 ± 2 Ma, constraining the temporal evolution of the ANS in the studied region into (1) the island-arc phase, represented by a metamorphic sample with an age of 729 ± 3 Ma. (2) the syn-orogenic phase, represented by calc-alkaline and alkaline granitic samples with ages ranging from 699 ± 4 Ma to 646 ± 2 Ma. These two phases indicate initiation of the compressional subduction regime in the CED since 729 ± 3 Ma and being dominated till 646 ± 2 Ma. (3) the post-orogenic phase, represented by metavolcanics, volcanic rocks, and alkaline plutonic samples with ages ranging from 623 ± 3 Ma to 570 ± 2 Ma. This phase suggests dominance of the compressional-to-extensional tectonic transition setting from 623 ± 3 Ma to 600 ± 1 Ma along with the Dokhan volcanism and activation of post-collision tensional regime activated at 582 ± 3 Ma. Our findings discourage the proposed dominance of the island-arc and syn-orogenic phases in the CED and the classical restriction of older magmatic activity to calc-alkaline granitic rocks and younger magmatic activity to alkaline granitic rocks. Additionally, we identified evidence of local magmatic sources by dating five grains with Mesoproterozoic (pre-Arabian–Nubian Shield) xenocrysts with ages ranging from 1549 ± 4 to 1095 ± 25 Ma.